Development and assessment of an integrated underground gasification system for cleaner outputs - Kahraman, Ugur; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this study, an underground coal gasification-based integrated multigenerational system is developed to generate multiple useful outputs, including electricity, heating, cooling, hydrogen, ethanol and sulfuric acid, for achieving cleaner applications and meeting the community needs. An application of this conceptually developed system is considered for a community as identified in Kutahya, Turkey. The proposed system is developed, modelled, and analyzed using thermodynamic-based, sensitive modeling tools and software packages. The effects of operating conditions such as oxygen, steam, as well as lignite feed rate, reference temperature, and gasifier temperature are investigated to evaluate the performance of the integrated underground coal gasification system. This research further aims to analyze the influence of varying system parameters and operational conditions on ethanol and hydrogen generation and increase energetic and exergetic efficiencies while reducing harmful product gas emissions. In this regard, many parametric studies of the underground coal-powered multigeneration system are conducted. According to the results, the integrated underground lignite gasification combined system's overall system energetic and exergetic efficiencies are found to be 68.8% and 66.56%, respectively.
Keywords: Cleaner production; Underground coal gasification; Energy; Exergy; Hydrogen; Ethanol; Sustainable society; COAL-GASIFICATION; THERMODYNAMIC ANALYSIS; MULTIGENERATION SYSTEM; HYDROGEN-PRODUCTION; EXERGY ANALYSES; LIQUEFACTION; Thermodynamics; Energy & Fuels